Edad optima de cosecha en variedades de caña de azucar para el Valle del Zulia - Carillo V., P.
(En, Es)
ilus., 7 ref.
Keywords: SACCHARUM OFFICINARUM; COSECHA; MADURACION; COLOMBIA; REGRESION CURVILINEA